Biomechanical Effect on Jack’s Test on Barefoot Position, Regular Socks, and Biomechanics Socks - Álvaro Gómez-Carrión; José Manuel Reguera-Medina; Manuel Coheña-Jiménez; Alfonso Martínez-Nova; Victor Manuel Jiménez-Cano; Rubén Sánchez-Gómez (Life, 2024)
The proper dorsal flexion movement of the first metatarsophalangeal joint (MTPJ) is crucial for an accurate gait. Restricted movement can disrupt the windlass mechanism, and Jack’s test is a tool to assess such alterations. Although running socks are commonly used, their influence on the windlass mechanism remains unclear. Therefore, the aim of this study was to measure the resistance to passive dorsal flexion of the first metatarsophalangeal joint (MTPJ) under three different conditions: barefoot, wearing regular socks, and wearing biomechanical socks, using a digital force gauge. Methods: The research involved a sample size of 30 subjects (14 men and 16 women), and Jack’s test was conducted using a digital force gauge and a lever system. Three conditions were measured, barefoot, with a regular sock, and with the biomechanical socks. Results: Statistically significant differences were observed when using biomechanical socks with orthopedic corrections during Jack’s test, as measured with the digital force gauge (13.33 N ± 3.54, p < 0.001). Conclusions: The utilization of biomechanical socks with a kinetic wedge, reinforced mesh in the medial longitudinal arch, and padding in the heel area results in a reduction of the force required, measured in newtons, to perform dorsal flexion of the first metatarsophalangeal joint (MTPJ) during Jack’s test compared to being barefoot or wearing regular socks.